If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 64 + -1x + 4 = 3(x + 4) Reorder the terms: 64 + 4 + -1x = 3(x + 4) Combine like terms: 64 + 4 = 68 68 + -1x = 3(x + 4) Reorder the terms: 68 + -1x = 3(4 + x) 68 + -1x = (4 * 3 + x * 3) 68 + -1x = (12 + 3x) Solving 68 + -1x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 68 + -1x + -3x = 12 + 3x + -3x Combine like terms: -1x + -3x = -4x 68 + -4x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 68 + -4x = 12 + 0 68 + -4x = 12 Add '-68' to each side of the equation. 68 + -68 + -4x = 12 + -68 Combine like terms: 68 + -68 = 0 0 + -4x = 12 + -68 -4x = 12 + -68 Combine like terms: 12 + -68 = -56 -4x = -56 Divide each side by '-4'. x = 14 Simplifying x = 14
| 12x=5x-35 | | -6.8=0.8(x+1) | | 2x-2=z+64 | | Ew=pfore | | (4x)(4x)-4x=2 | | -8m^2+26m-21=0 | | 11-3-2*w= | | x+3x+3x=65 | | 3x+2(x-3)=214 | | -9x=-24 | | X+3y+7=0 | | 1.17=.63x-1.08 | | x-9/4=-5 | | 6(7-y)+4=-4(y-3)-11 | | 2(2n-5)=12+2(n+8) | | 26=6+10-3g | | X+ax=0 | | z^2+(2+i)*z+(3+11i)=0 | | 6(2x+9)=12x-10 | | f(x)=kx^2-5x+3 | | 18s-17=13s-9 | | -ay-ay=0 | | (5+2i)(-6-6i)= | | 3a+5=9x-7a | | X=6-1.25y | | -2/3(12c-9)+14c=0 | | 14b+10b=180 | | Ay-2y=0 | | (y+6)(y+3)=0 | | 4(4-w)=3(2w+r) | | x^2+y^2+5x-8y-4=0 | | f(x)=3x^4+4x^3-5x+8 |